PERANCANGAN SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS DARI SEWA KAMAR MENGGUNAKAN GOOGLE SPREADSHEET PADA DEPARTEMEN KEUANGAN PT CIHAMPELAS CERDAS MANDIRI - Anne Prisillia; Mukaram Mukaram (Ebiz Prima Nusa, 2023)
PT Cihampelas Cerdas Mandiri is an accommodation company or business entity engaged in accommodation services or room rentals. The cash income system for renting rooms at PT Cihampelas Cerdas Mandiri is still done manually, while PT Cihampelas Cerdas Mandiri has established two hotels, namely Cihampelas Hotel 1 and Cihampelas Hotel 2, with the head office located at Cihampelas Hotel 2. This raises various problems. Companies often face problems with cash income systems from room rentals that are less effective and efficient, so that it can affect the achievement of the Daily Income Report. In this context, a computerized and online cash income accounting information system has been created to facilitate the verification process of calculating cash income from room rentals, as well as reducing the frequency of errors in calculating cash income from room rentals. The purpose of this final report is to improve performance in calculating cash income from room rent to be more effective and efficient in the future. In addition, this Final Project report is a solution for companies in the process of calculating cash income from room rentals computerized using Google Spreadsheets.